2020
DOI: 10.1371/journal.pone.0226312
|View full text |Cite
|
Sign up to set email alerts
|

Significance of skull osteoporosis to the development of peritumoral brain edema after LINAC-based radiation treatment in patients with intracranial meningioma

Abstract: Background and purposeDisruption of the tumor-brain barrier in meningioma plays a critical role in the development of peritumoral brain edema (PTBE). We hypothesized that osteoporotic conditions may be associated with PTBE occurrence after radiation in patients with intracranial meningioma. OPEN ACCESS Citation: Lee R-H, Kim JM, Cheong JH, Ryu JI, Kim YS, Han M-H (2020) Significance of skull osteoporosis to the development of peritumoral brain edema after LINAC-based radiation treatment in patients with intrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previously, it was revealed that arachnoid trabeculae and granulations are composed of type 1 collagen [ 27 ]. Based on the above concept, we have previously reported clinical studies that suggest a possible association between osteoporotic conditions and arachnoid trabeculae integrity because bone and arachnoid trabeculae are composed of type 1 collagen [ 7 , 17 , 28 ]. Therefore, because osteoporosis is more common with increasing age, it is possible to postulate that the elderly may have a greater chance of having weakened arachnoid trabeculae integrity which constitutes the brain-meningioma interface compared to younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was revealed that arachnoid trabeculae and granulations are composed of type 1 collagen [ 27 ]. Based on the above concept, we have previously reported clinical studies that suggest a possible association between osteoporotic conditions and arachnoid trabeculae integrity because bone and arachnoid trabeculae are composed of type 1 collagen [ 7 , 17 , 28 ]. Therefore, because osteoporosis is more common with increasing age, it is possible to postulate that the elderly may have a greater chance of having weakened arachnoid trabeculae integrity which constitutes the brain-meningioma interface compared to younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-brain barrier disruption in meningioma is crucial for PTBE formation [ 1 ]. We recently reported a possible association between PTBE and the brain-meningioma interface and meningioma volume after radiation therapy [ 7 ]. In that study, because radiation may aggravate the damaged tumor-brain contact interface, we hypothesized that greater damage to the tumor-brain interface due to large tumor volume would be associated with a higher probability of tumor-brain barrier disruption leading to PTBE after radiation therapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study included patients from the NOVALIS registry. The NOVALIS registry was designed for prospective research of patients who received radiation treatment in our hospital [ 8 ]. We investigated all consecutive patients with intracranial meningioma from the registry who underwent linear accelerator (LINAC)-based radiation treatment for the first time at our hospital from July 7, 2014 to September 30, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed radiation technique in our hospital was previously described [ 8 ]. The NOVALIS Tx system (Varian Medical Systems, CA, USA; Brainlab, Feldkirchen, Germany) was used to treat all meningioma patients.…”
Section: Methodsmentioning
confidence: 99%
“…Birnbaum BA et al reported that variations in HU values are very small (range of 0-20 HU) between five CT scanners including Philips and Siemens [12]. We previously reported detailed methods for measuring HU values at each of four lines on the frontal cancellous bone between the right and left coronal sutures on axial CT slices at the point where the lateral ventricles disappear (Fig 1A) [13,14].…”
Section: Measurement Of Frontal Skull and Iop Humentioning
confidence: 99%